Strategic Public Relations to Build Public Trust in Islamic Boarding Schools: A Case Study in Indonesia - Hikmah Eva Trisnantari; Moh. Gufron; Putri Rahayu Ningsih (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2024)
This study aims to analyze the role of public relations (PR) management in enhancing public trust in Islamic educational institutions, focusing on Pondok Pesantren Madrasatul Qur'an (MQ) Tebuireng Jombang. A qualitative phenomenological research design was employed to capture stakeholders' lived experiences and practices in managing PR activities. Data were collected through in-depth interviews, observations, and documentation, and subsequently analyzed through data condensation, presentation, and conclusion drawing. The findings reveal that PR strategies at MQ Tebuireng are implemented through several key programs. These include journalism training to nurture students' communication skills, social media management to broaden institutional outreach, publication of students' works to showcase pesantren achievements, and public speaking training to improve students' confidence in representing the institution. In addition, word-of-mouth promotion involving alums, parents, and teachers is vital in expanding the pesantren's reputation into the broader community. Leadership initiatives also significantly promote a positive institutional image and encourage participation in social activities. The study concludes that effective and strategic PR management enhances public trust and strengthens the institution's sustainability. The implication is that Islamic boarding schools must integrate structured and professional PR programs into their management systems to improve credibility, foster social legitimacy, and ensure long-term institutional development.